OS REPÓRTERES DO BRASIL PRÉ-COLONIAL: gêneros e formatos folkcomunicacionais - Ferreira, Fábio Gonçalves (2013)
This work is an inventory about the existence of means of communication in Brazilian territory, on the period before its discovery by the European colonists (before 1500). The main goal of this survey is to trace how they used to produce their messages and how they established their folk communication channels between the Indians and the tribes that existed in pre-colonial Brazil. We also intend to study the elements of folk communication adopted by the Indians and to draw a parallel, coming from the starting point of the concepts of the pernambucano (a person who is born in the city of Pernambuco) researcher Luiz Beltrão and his disciples created. This will result in the application and updated review of the typology of folk communication that was used in that historical period. The study was made with empiric foundation due to observation, which shows the importance of Indian communication in the context of Brazil, where people lived in society groups and had their values reduced and destroyed by the colonists. The methodology used in the work was able to embrace a confluence of techniques, such as: bibliographic research (books, articles and journals), documental research (in specialized magazines, printed and virtual publications). All this material was gathered in public and private collections.